2018
DOI: 10.4172/2155-9600.1000660
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Skin Conditions by Consumption of Traditional Japanese Miso Soup and Its Mechanism

Abstract: The present study was undertaken to determine the beneficial effects of miso soup consumption on the skin. The women were divided into two groups: the first group consumed three bowls of miso soup per day (miso-consuming group) and the second group consumed three bowls of soup per day without miso (non-miso-consuming group or control group). The women in both groups continued their respective routines every day. Before and after the 2-week trial, the stratum corneum water content, elasticity, sebum amount and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…β-GCase activity was determined using 4-methylumbelliferyl β- d -glucopyranoside [ 1 ]. Human keratinocytes cultured for three days in the 96-well plate were washed twice with PBS, and 30 μL of 0.01 mol/L acetate buffer (pH = 5.0) and 40 μL of a 5 mmol/L 4-methylumbelliferyl β- d -glucopyranoside solution were added.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…β-GCase activity was determined using 4-methylumbelliferyl β- d -glucopyranoside [ 1 ]. Human keratinocytes cultured for three days in the 96-well plate were washed twice with PBS, and 30 μL of 0.01 mol/L acetate buffer (pH = 5.0) and 40 μL of a 5 mmol/L 4-methylumbelliferyl β- d -glucopyranoside solution were added.…”
Section: Methodsmentioning
confidence: 99%
“…Rice miso contains many ingredients derived from rice koji and has been a valuable source of nutrition since ancient times. We found that ingesting rice miso improved the moisture content in cheek stratum corneum, skin viscoelasticity, and texture [ 1 ]. Furthermore, the effect of miso extract on ceramide synthesis in epidermal keratinocytes was examined in cultured cells, and the mRNA expression and activity of glucocerebrosidase (β-GCase) in these cells increased when the cells were treated with miso extract [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A good diet is fundamental to improving skin disorders that cannot be resolved with cosmetic products. Consumption of foods that can positively affect the skin, such as collagen peptides [43], hyaluronan [44], N-acetylglucosamine [45], rice-derived glucosylceramide [46], royal jelly [47], and miso [48], are essential for maintaining the internal and/or external beauty of the skin.…”
Section: Inner Beautymentioning
confidence: 99%